The Italian Language Today - Lepschy, Anna Laura; Lepschy, Giulio (Rowman & Littlefield Publishers, 1998)
Italian as a national spoken language is a new experience for Italians; until very recently it was normal for the majority of the people to speak in a dialect, and Italian was a literary language used only by a minority. The first section of this book provides an outline of the language, and a sketch of the dialects. The authors also describe the formation of the modern standard language in its varieties (regional, social, and occupational). Part two is a reference grammar of contemporary educated Italian, presented in the way it is actually used, rather than according to traditional prescription. The book concentrates on contemporary usage and will enable the reader to understand and use appropriately a wide range of expressions, characterized where necessary according to their level of formality or their regional nature. The illuminating combination of historical perspective and contemporary grammer make this a unique contribution to Italian linguistics, and an invaluable reference book for all students and scholars in the field of Italian. The second edition has been revised throughout to bring it completely up to date.